Estudio de factibilidad para la producción y comercialización de compota de zapallo para mejorar la nutrición infantil de Quevedo - Vera Zambrano, Alba Verónica (2013)
As time passes, the production companies have had to develop several tools to fully meet the progressive needs of consumers, as well as increase profitability in the global financial daily that requires better strategies to achieve greater competitiveness in the market. However, companies should not only base their strategies and interests in achieving customer satisfaction, they should consider all the success would mean nothing without accepting that their employees as a cornerstone of its operation It is noteworthy that the profitability of a company or institution will always be linked with the level of productivity that employees perform and this will depend on the level of training they have to do their jobs and have an effective power. Thus arises the initiative to conduct a feasibility study for the production and marketing of pumpkin puree in the city of Quevedo to provide an alternative solution to the problem of child malnutrition. This proposal will determine the technical and organizational microenterprise to evaluate financial investment to make, identify potential customers and consumers, their preferences and their purchasing power, and certainly more important to define the contribution of microenterprise society to analyze what impacts it will have on already generating new jobs in the province of Los Ríos.